THE The Use of Injectable Platelet-Rich Fibrin As an Alternative Treatment for Interdental Papilla Reconstruction in Black Triangle Case - Mayangjati, Nastiti; Fawzan Nur Ramadhan; Vincensia Maria Karina (Lembaga Penelitian Universitas YARSI, 2024)
Introduction: Interdental papilla is triangular soft tissues that fill the gaps between teeth andfunction as protective periodontal tissues and are important in terms of aesthetics, ifinadequate, they will form black triangles, which are blackish areas between teeth. Non-surgical treatment of black triangle is preferred by patients as it is painless. Injectable Platelet-Rich Fibrin (i-PRF) is a platelet concentrate derived from the patient's blood that does notcause immunological reactions and contains growth factors for remodeling the interdentalpapilla. Case Report: A 20-year-old female patient, systemically healthy, came to Prof.Soedomo UGM Dental Hospital with complaints that the gums of the middle part of her upperteeth had a blackish area and disturbed her confidence. An objective examination was carriedout including, gingival biotype, black triangle area, and radiographs, so it was concluded thatthe black triangle was classified as class I Nordland and Tarnow and interdental papillareconstruction to correct the black triangle could be planned. The patient refused surgery so i-PRF can be used as an alternative non-surgical treatment. The black triangle closed completelyafter the i-PRF injection was given. Discussion: I-PRF has the ability to accelerate cellproliferation and migration as well as angiogenesis so that it can modulate fibroblastregeneration in the interdental papilla area. Conclusion: The use of i-PRF can be an alternativenon-surgical option for the treatment of interdental papilla reconstruction.